The Big Five factors of personality model: A study of history, evolution, and areas of application in the digital context - El-Yazidi, Reda (Arab Journal for Sciences and Research Publishing, 2024)
This study highlights the evolution of the Big Five Factors of Personality model as well as the theories offered by psychologists (Allport, Cattell, Eysenck, Costa, and McCrae) to understand personality, with an attempt to explore the application of the model in the digital context. The study aims to explain the importance of the model in analyzing the five basic traits that constitute human personality (neuroticism, extraversion, openness, agreeableness, and conscientiousness) and in predicting human behavior. The study relied on the historical and analytical approaches in order to evaluate the literature and present the main evolutions in psychology of personality, starting with the first personality tests, which appeared in the period between and after the First and Second World Wars, to the stage of inventing the model and adopting it as a powerful scientific tool to measure personality and characterize the differences between individuals. The results of the literature review indicate that the model is effective in profiling, digital behavior analysis, and microtargeting in commercial advertising and political campaigns. The study recommends further scientific research on the ethical and legal issues arising from the use of the model in violating individuals' privacy and using their personal data in the digital world.
Keywords: Big Five Factors of personality; model; trait; profiling; predicting behavior; digital context